The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1590/s0103-90162010000500003
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of a tractor engine using mineral and biodiesel fuels blended with rapeseed oil

Abstract: One of the most unfavourable characteristics of crude vegetable oil when used as the fuel is the high viscosity. To improve this weakness, oil can be blended with mineral diesel or biodiesel fuels. This study was designed to evaluate how the use of mineral diesel or biodiesel blend with cold pressed rapeseed (Brassica napus) oil affects the engine power, torque and fuel consumption. A tractor equipped with direct injection, water cooling system and three-cylinder diesel engine was used for the experiment. Fuel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
3
0
1
Order By: Relevance
“…MAZIERO et al (2006) found increased, on average, 22% of the power generated per unit of fuel when worked with sunflower biodiesel. GODESA et al (2010) found an increase in the power generated by fuel unit of 6.5% with an increase of 50% of biodiesel. NIETIEDT et al (2011) reported an increase of 10.9% with B100 compared to B5.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…MAZIERO et al (2006) found increased, on average, 22% of the power generated per unit of fuel when worked with sunflower biodiesel. GODESA et al (2010) found an increase in the power generated by fuel unit of 6.5% with an increase of 50% of biodiesel. NIETIEDT et al (2011) reported an increase of 10.9% with B100 compared to B5.…”
Section: Resultsmentioning
confidence: 93%
“…Nevertheless, it is known that in certain proportions of the two fuels (mineral diesel and biodiesel), there are significant change on engine performance and emission levels. Some studies show that the use of pure biodiesel in vehicle diesel cycle engines reduces the torque and consequently the power generated (MAZIERO et al, 2006;OZSEZEN et al, 2009;BUYUKKAYA, 2010;FIORESE et al, 2011;NIETIEDT et al, 2011) and increases the time consumption and minimum specific consumption (GODESA, et at. 2010;NIETIEDT et al, 2011;REIS et al, 2013;ÖZENER et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The results follow the same trend as that reported by Perin et al (2017), who found that the specific consumption increased by 7.10% and 9.33% for B20 and B50, respectively, compared to B10. Godeša et al (2010), on the other hand, observed corresponding increases in the specific consumption of 1.25% and 2.5% for B20 and B30, respectively.…”
Section: Resultsmentioning
confidence: 90%
“…Num cenário cada vez mais frequente de preços elevados dos combustíveis fósseis e de mudanças climáticas devido à degradação ambiental causada pelas emissões gasosas, o uso da biomassa, na forma dos óleos vegetais e os biocombustíveis, contribuem para a redução desses problemas, diminuindo significativamente a carga poluente emitida, se tornando uma fonte de energia renovável e uma alternativa ao uso do óleo diesel (Godesa et al, 2010;Silva et al, 2012;Dias et al, 2014).…”
Section: Introductionunclassified